2018
DOI: 10.1111/ctr.13239
|View full text |Cite
|
Sign up to set email alerts
|

Graft versus host disease after multivisceral transplantation: A UK center experience and update on management

Abstract: Graft versus host disease (GVHD) following transplantation of an intestine-containing graft occurs more frequently than with other solid organ transplants and is known to have a poor outcome. The presentation differs from other solid organ transplants, as the gastrointestinal tract is not involved following intestinal transplant. Diagnosis is based on clinical symptoms arising due to native tissue damage and the detection of donor T lymphocytes in circulating blood (T-cell chimerism). The ideal treatment strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…GVHD was unresponsive to steroids, multiple immunosuppressive agents, biologics, in addition to ECP. In adults, ECP use has been reported in GVHD with good outcomes following multivisceral organ transplantation, 13 liver transplantation, 14 and simultaneous pancreas‐kidney transplantation 15 . Houston et al reported the use of ECP in a 28‐year‐old man on Days 62 and 67 post multivisceral organ transplantation with reduction in chimerism over 9 days; however, the patient died of sepsis on Day 73 16 .…”
Section: Discussionmentioning
confidence: 99%
“…GVHD was unresponsive to steroids, multiple immunosuppressive agents, biologics, in addition to ECP. In adults, ECP use has been reported in GVHD with good outcomes following multivisceral organ transplantation, 13 liver transplantation, 14 and simultaneous pancreas‐kidney transplantation 15 . Houston et al reported the use of ECP in a 28‐year‐old man on Days 62 and 67 post multivisceral organ transplantation with reduction in chimerism over 9 days; however, the patient died of sepsis on Day 73 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic targets that warrant further investigation include IL-6, rho-associated coiled-coil-containing protein kinase-2 (ROCK2), Bruton's tyrosine kinase, and colony-stimulating factor 1 receptor (CSF-1R). 82,[89][90][91][92][93] GvHD in ITx poses unique challenges in early detection, diagnosis, and treatment. Diagnosis rests on the combination of clinical and histopathological findings in ≥1 target organ systems including the skin, native intestine, liver, respiratory tract, and bone marrow, among others.…”
Section: Lessons Learned From Hsct and Potential For Future Pharmacol...mentioning
confidence: 99%
“…88 Multiple studies have demonstrated the efficacy of ECP in refractory GvHD after HSCT; however, limited studies have shown the effectiveness of ECP in GvHD after ITx. 77,85,86,89 Merola et al 77 described 2 case reports demonstrating the potential benefits from ECP. Decreased chimerism in both patients, in addition to full recovery in one patient, was described.…”
Section: Current Operative and Pharmacological Approaches To Preventi...mentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs when immunocompetent lymphocytes from the transplanted organ mount an immune response against host antigens, causing cytotoxic damage to cells. Small bowel and multi‐visceral transplants, which contain a relatively large burden of donor lymphoid tissue, have the highest incidence of GVHD 2,3 . However, it is most commonly seen in the setting of liver transplantation given the higher frequency of this procedure 1,4 .…”
Section: Introductionmentioning
confidence: 99%